2020
DOI: 10.1007/s13178-020-00436-y
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Young Victims of Unwanted Sexual Experiences: a Gender Comparison Using a Swiss National Survey

Abstract: Purpose Youths are particularly at risk of experiencing sexual victimization but research tends to focus on the most violent forms (i.e. rape or child sexual abuse) and on female cases. This study aimed at identifying factors associated to different types of unwanted sexual experiences (USE) among young females and males as well as estimating probabilities of experiencing sexual victimization among gender.Methods Data were drawn from a cross-sectional survey on sexual health and behaviors using a nationally re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…We further provide an analysis of associated factors. Our findings suggest that being female, young, non-heterosexual, having a higher number of sexual partners and financial difficulties are associated with an increased likelihood of sexual victimization which is in line with past research [9,20,[24][25][26]. The fact that the youngest age group in our study was most likely to be victimized in the past year is in line with past research that showed young adults and adolescents are especially at risk of sexual victimization [7,19].…”
Section: Associated Factorssupporting
confidence: 92%
See 1 more Smart Citation
“…We further provide an analysis of associated factors. Our findings suggest that being female, young, non-heterosexual, having a higher number of sexual partners and financial difficulties are associated with an increased likelihood of sexual victimization which is in line with past research [9,20,[24][25][26]. The fact that the youngest age group in our study was most likely to be victimized in the past year is in line with past research that showed young adults and adolescents are especially at risk of sexual victimization [7,19].…”
Section: Associated Factorssupporting
confidence: 92%
“…The studies presented above show that women generally have a higher risk of sexual victimization than men. Moreover, previous research shows that this risk seems to be higher among young people [ 7 , 19 , 24 ] and non-heterosexual people [ 25 ]. Other factors related to sexuality that are associated with sexual victimization are, among others, early sexual initiation and more lifetime sexual partners [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Progressive scientific knowledge has shown that domestic violence is a gendered phenomenon, with differences in the magnitude, dynamics, and contexts underpinning domestic violence against women and against men [9]. Also, domestic violence is a quite transversal phenomenon across society, affecting all ages and any socioeconomic or cultural group, with complex and deeply entrenched underlying causes, and is often not officially reported [2,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…We assessed three types of undesired sexual experiences: having ever accepted sexual intercourse without really wanting (never, once, several times), unwanted sexual intercourse or contact (never, once, several times with the same/various persons) and sexual assault/abuse (yes/no). Having ever accepted sexual intercourse without really wanting may be categorized in the sexual compliance group (Auderset et al, 2021 ) (i.e. the act of consenting to unwanted sexual activity (Darden et al, 2019 )).…”
Section: Methodsmentioning
confidence: 99%